Decision Support System For The Determination Of Lecturers Using The Weighted Product (WP) Method (Case Study: IPA Study Program FKIP UNIB) - Sanjaya, Aldy; Maryaningsih, Maryaningsih; Sartika , Devi (Jurnal Komputer Indonesia, 2022)
The problem faced today is the ineffectiveness of recruiting teaching assistants. Considering the selection of lecturer assistants must be right because to become a lecturer assistant is not easy. A lecturer assistant is required to be professional in providing values or solutions when problems occur. Seeing this situation, in the recruitment of teaching assistants a Decision Support System (SPK) is needed so that the recruitment of teaching assistants can be carried out more accurately. One method of decision support system is Weighted Product (WP). This method is the method used in ranking the simplest values by using multiplication to connect the attribute rating where the rating must be raised first with the weight of the attribute in question. Application of the Decision Support System for determining teaching assistants using the Weighted Product (WP) method, can be used to determine the best teaching assistants based on criteria, namely course grades, final GPA scores, attendance scores, communication skills scores, material mastery scores and discipline scores during lectures. Based on the results of research from 15 samples used in the Decision Support System for determining lecturer assistants using the Weighted Product (WP) method, those who are entitled to become a lecturer assistant are on behalf of Rizky Yeleni with a value of 0.0819. This application is made using Visual Basic Net programming language with SQL server database. Based on the results of system testing, it can be concluded that the functionality of the application for determining lecturer assistants using the Weighted Product (WP) method has been running as it should and can help determine who is entitled to become a lecturer assistant which can be seen in the output.